FEATURES OF NEUROHUMORAL RESPONSE TO STRESS IN PATIENTS WITH THORACOABDOMINAL INJURIES AND ALCOHOL INTOXICATION - E. P. SOROKIN; YE. G. BUTOLIN; Ye. V. SHILYAEVA; V. G. IVANOV (Кубанский научный медицинский вестник, 2017)
Aim. To identify specific neurohumoral response to stress in patients with thoracoabdominal injuries and alcohol intoxication. Materials and methods. 244 patients with thoracoabdominal injuries were examined. 183 injured had the signs of alcohol intoxication, when they were admitted at the hospital. Blood pressure and heart rate were measured. Kerdo index was calculated and then evaluated over time. Venous blood samples were taken from 24 male patients before and after induction of anesthesia, during surgery, after 1, 6, 12, 24 hours. Cortisol, insulin, TTH, STH and prolactin were determined in the samples. Results. Kerdo index decreases during the time of the treatment. Kerdo index changes equally in patients with alcohol intoxication and without it. Cortisol level for the injured with alcohol intoxication increased moderately, but for longer time. The concentration of insulin, STH and TTH do not go beyond the reference values. In patients without signs of alcohol intoxication all of these biological substances have a tendency to a short-term (up to 12 hours after surgery) increase. The ratio of cortisol/insulin was significantly higher, in case the injured had signs of alcohol intoxication, indicating the predominance of catabolism and efficient use of lipids. Conclusion. An alcohol intoxication is a factor influencing the development of stress-induced response and reducing its severity in patients with thoracoabdominal injuries.